Nursing Knowledge in the 21st Century: Domain-Derived and Basic Science Practice-Shaped. (January 2019) - Roy, Callista
Abstract : Some have described that nursing is at a crossroads that necessitates finding ways to balance knowledge development that is philosophical and conceptual/theoretical with the empirical inquiry, particularly of the developing related biologic sciences. This article sets a direction for nursing knowledge development that is domain-driven. The central role of nursing theory in attaining the common goals of nursing is envisioned. Recommendations include that grand theories, middle-range theories, and practice theories in tree-like fashion feed into the common goal of humanization; that all teaching tools in nursing begin with common goals and describe nursing theories as contributing to these goals; that theory-practice alliances are central in filling out the envisioned domain-driven knowledge and integrating this with practice-shaped basic sciences.